Pesquisa dos genes icaD e bap de adesão intercelular bacteriana e formação de biofilme por Staphylococcus aureus e Staphylococcus coagulase-negativa isolados de mastite bovina - Salina, Anelise [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Staphylococcus aureus is common in intramammary infections, which often become chronic, among other factors, by the ability of this bacteria to produce biofilm. The objective was to verify the production of biofilm capacity in strains of S. aureus and coagulase negative Staphylococcus (CNS), derived from clinical and subclinical bovine mastitis. A total of 100 strains of S. aureus and 100 strains of CNS were isolated from cases of subclinical and clinical mastitis in two properties of São Paulo State. The screening test of subclinical mastitis was the California Mastitis Test (CMT). Somatic Cell Count (SCC) and microbiological culture of milk samples was performed. We researched the presence of icaA, icaD and bap genes by the Polymerase Chain Reaction (PCR) and phenotypic characterization on congo red agar (CRA) and biofilm production on plates. There was no observed relationship between the intensity of the reaction to the CMT and SCC. The mean of SCC was 2.88 ± 0.59 for S. aureus and 2.71 ± 0.35 for CNS. There was no significant statistical between SCC values for strains containing the presence of those researched genes. But the means of the CCS values were higher in isolates that containing such genes. The frequency icaA, icaD and bap in S. aureus were 82%, 83% and 58%, respectively. It was observed that the 83% of S. aureus isolates that had icaD, 82 (98.8%) also had icaA, with statistical significance in the Fischer's exact test (p <0.001). In association between icaA and bap genes, was also observed significant association, for the 82 strains that showed icaA, we observed the presence of bap in 56 (68.3%). Of the 83 strains that containing the icaD gene, 56 (67.5%) of them was also detected the presence of bap gene. There was no agreement between the phenotypic tests (K<0.2). The positivity on congo red agar revealed that 25% of S. aureus strains produced in vitro biofilm. In the adhesion test plates, this number was lower, with ...

Staphylococcus aureus é comum em infecções intramamárias, que frequentemente se tornam crônicas, entre outros fatores, pela capacidade dessa bactéria em produzir biofilme. Objetivou-se verificar a capacidade produtora de biofilme em estirpes de S. aureus e Staphylococcus coagulase negativa (SCN), oriundas de mastite bovina clínica e subclínica. Um total de 100 cepas de S. aureus e 100 cepas de SCN foram isoladas de casos de mastites subclínicas e clínicas em duas propriedades do Estado de São Paulo. O teste de triagem da mastite subclínica foi o California Mastitis Test (CMT). Foi realizada Contagem de Células Somáticas (CCS) e cultivo microbiológico das amostras de leite. Pesquisou-se a presença de genes icaA, icaD e bap pela Reação em Cadeia pela Polimerase (Polimerase Chain Reaction - PCR) e caracterização fenotípica no ágar Vermelho Congo (VC) e teste de produção de biofilme em placas. Não houve relação entre a intensidade da reação ao CMT e a CCS. A média de CCS foi de 2,88±0,59 para S. aureus e 2,71±0,35 para SCN. Não houve significância estatísticas entre os valores de CCS para estirpes que continham a presença dos genes pesquisados. Porém as médias dos valores de CCS foram maiores nos isolados que continham tais genes. As frequências de icaA, icaD e bap em S. aureus foram de 82%, 83% e 58%, respectivamente. Observou-se que dos 83 isolados de S. aureus que apresentaram icaD, 82 (98,8%) também apresentaram icaA, com significância estatística no Teste Exato de Fischer (p<0,001). Na associação entre os genes icaA e bap, também foi observada associação significante pois das 82 estirpes que apresentaram icaA, foi possível observar a presença de bap em 56 (68,3%). Das 83 linhagens que continham o gene icaD em 56 (67,5%) delas, também foi detectada presença do gene bap. Não houve concordância entre os testes fenotípicos (K<0,2). A positividade no vermelho congo revelou que 25% das...
Keywords: Staphylococcus aureus; Mastite; Vermelho congo; Biofilme; Saúde pública; Reação em cadeia da polimerase; Staphylococcus; Biofilms